Pengembangan Desa Wisata Telaga Pelemwatu Melalui BUMDes Di Desa Pelemwatu Kabupaten Gresik - Muhammad Thoriq Asrori; Endang Indartuti; Dida Rahmadanik (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This research examines the development of the Telaga Pelemwatu Tourism Village through BUMDes in Pelemwatu Village, Gresik Regency. Using descriptive qualitative methods, this research analyzes tourism development based on six indicators: Attraction, Accessibility, Facilities, Lodging, Activities and Supporting Services. The research results show that the development of this tourist village has been effective in attracting tourists with its unique appeal, but still faces challenges in terms of accessibility and infrastructure. Even though it has succeeded in improving the welfare of local communities and preserving culture and the environment, improvements are still needed in several aspects such as promotion, maintenance of facilities and improvement of supporting services. This research concludes that the development strategy for the Telaga Pelemwatu Tourism Village can be used as a model for the development of other tourist villages in Indonesia, noting that there is a need for continuous improvement to meet visitor needs and ensure long-term sustainability.